EVALUASI PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN KABUPATEN BUTON TAHUN 2014 - Matu, Alimuddin (JI@P, 2015)
Musrenbang an assessment of the most important results of the proposed program priorities of the community. Musrenbang is a forum to express the aspirations of the people, in the development process that will be implemented by the government. Musrenbang is the process of advancing every area ranging from rural/village, district, district/municipal, provincial and central. This study aims to determine the Musrenbang Buton 2014. This study used a qualitative approach perspective. Qualitative research conducted in the state of nature (natural setting). The approach used is a phenomenological approach (post-positivist), which is described with the understanding than expected, with the working hypothesis than pengujiann strict hypothesis, and the reciprocal relationship between the researcher and the object of study rather than a separate observation on the part of the analyst. Implementation Musrenbang in Buton has gone through various stages, the procedures for making, Control, and Evaluation of the Implementation of the Regional Development Plan. In general Musrenbang Buton can run well, although not in spite of obstacles and barriers, both the organizers and of the implementation. From the organizers, BAPPEDA as agency responsible for the implementation of planning forums without any significant obstacles. Musrenbang can be a strategic activity that is expected to accommodate input of citizens in local development planning as a form of public participation in the development of bottom-up to be harmonized with the activities of the development programs of the government that is top down. Musrenbang should be a strategic forum, however, from year to year tends to decline in quality due to the emergence of community saturation. BAPPEDA as a planning agency should facilitate the establishment of a facilitator musrenbang at village / district and sub-district, preceded by a training/ technical briefing before the circuit musrenbang implemented. In addition, the need for involvement of academics, community leaders, NGOs, and relevant stakeholders in the formulation of a preliminary draft RKPD through public consultation into the draft RKPD as material Musrenbang District. Keywords: Evaluation, Musrenbang, BAPPEDA